KOMUNIKASI ANTAR BUDAYA ETNIS TIONGHOA DAN ETNIS MINANGKABAU DI KAMPUNG CINA KELURAHAN NUNANG DAYA BANGUN KECAMATAN PAYAKUMBUH BARAT - Laila Kusuma (Jurnal Komunikasi, 2023)
Payakumbuh has a large variety of ethnicities, races, religions and cultures. Including several ethnic groups in the West Payakumbuh sub-district, there are several ethnic groups including Minangkabau, Chinese, Batak, and Javanese. The Chinese and Minangkabau ethnic groups have several differences, such as differences in the use of language, and differences in values and cultural norms. Differences like this can affect the way these two ethnicities communicate, such as misunderstandings and conflicts between the two. However, researchers found collaboration and adapted to effective ways of communication to build a common understanding between the two. The type of research used in this research is a type of research with a descriptive qualitative approach, the data collection methods used are observation, interviews, and documentation. The results of the study can be concluded, first, how is communication based on the intercultural Chinese and Minangkabau ethnicities, in terms of cultural dimension theory, there is an attitude of mutual understanding and acceptance of differences, both in terms of language, religion, culture and norms. Then seen from the perspective of cultural adaptation theory, being able to adapt to the existing cultural differences, between the ethnic Chinese and the ethnic Minangkabau. The two supporting factors for communication between ethnic Chinese and Minangkabau are similarities in using language, closeness, mutual respect for differences, a good environment, helping each other and having a high sense of kinship